Polygala tenuifolia Willd. Extract delays non-alcoholic fatty liver disease progression in rats via the COX2 and PERK-elF2α-ATF4 pathway - Sun, Zhiliang; Zhou, Zhongshi; Liao, Kezheng; Liu, Yanju; Liu, Yanyun; Wang, Chaoyang; Zhang, Zhihua; Wen, Li (Frontiers in Pharmacology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD), a chronic liver disease posing a severe threat to human health, currently lacks specific therapeutic drugs. Our previous studies have demonstrated that Polygala tenuifolia Willd. Extract (EPT) can significantly suppress the PGE2 inflammatory pathway, thereby exerting anti-inflammatory and antioxidant effects, as well as improving lipid metabolism. These findings suggest that EPT might hold potential value for the prevention and treatment of NAFLD.PurposeThis study aims to investigate the role of EPT in NAFLD and its multi - target synergistic mechanisms, and to preliminarily explore its impact on the early progression of NAFLD.MethodsThe detection of EPT components in rat blood was performed by UPLC-MS/MS. A rat NAFLD model was established using a high-fat emulsion gavage method, and pathological changes in liver tissue were assessed via H&E, Oil Red O, and Sirius Red staining. RNA-seq, immunohistochemistry, RT-qPCR, and Western blotting were used to evaluate the expression of cyclooxygenase 1 (COX1), cyclooxygenase 2 (COX2), inflammatory factors (IL-1, IL-6, TNF-α), oxidative stress-related proteins in the KEAP1 pathway, proteins involved in the protein kinase R-like endoplasmic reticulum kinase (PERK) pathway, and apoptosis-related proteins (Bcl-2 and Caspase-3).ResultsEPT significantly attenuated the histopathological alterations in liver tissue and ameliorated lipid accumulation in the livers of NAFLD rats. RNA-seq identified differential changes in the arachidonic acid metabolism, inflammatory, and endoplasmic reticulum-related pathways. Immunohistochemistry showed that EPT reversed the elevated expression of COX2, the ER stress marker GRP78, and PERK in the liver tissue of model rats. RT-qPCR and Western blot analyses confirmed that EPT reduced the expression of COX1, COX2, IL-1β, IL-6, TNF-α, and KEAP1, while increasing Nrf2 and HO-1 levels. Furthermore, EPT downregulated GRP78, PERK, p-PERK, eIF2α, p-eIF2α, ATF4, CHOP, Bcl-2, and Caspase-3.ConclusionThese results suggest that EPT might exert anti - inflammatory and antioxidant effects by modulating the COX2 pathway in NAFLD rats, downregulate the ER stress PERK - eIF2α - ATF4 signaling pathway, alleviate ER stress, inhibit apoptosis, and delay NAFLD progression.